USE OF EVIDENCE-BASED PRACTICE BY NURSES IN THE HOSPITAL SERVICE - Juliana de Oliveira Musse Silva; Leila Cristina Oliveira Santos; Alef Nascimento Menezes; Abel Lopes Neto; Luciana Simões de Melo; Flávia Janólio Costacurta Pinto da Silva (Universidade Federal do Paraná, 2020)
Objective: To describe the practices, attitudes and knowledge of hospital nurses about Evidence-Based Practice. Method: Descriptive study with 124 nurses from a university hospital in Sergipe, Brazil. The Evidence-Based Practice Questionnaire was applied between January and February 2019, and data were analyzed using Shapiro-Wilk, Kruskal-Wallis and Post hoc tests. Results: Of the total participants, 86.3% are female; the mean age is 34.5 years and the time since graduation ranged from five to ten years. The final average score for the Evidence-Based Practice Questionnaire was 115.9, indicating positive attitudes of nurses related to Evidence-Based Practice. Conclusion: Nurses' attitudes are based on scientific results. However, the best evidence is not always used to support professional practices. Disseminating the appropriate use of research in Nursing contributes to patient safety, permanent education and quality of care.